2003
DOI: 10.1523/jneurosci.23-24-08532.2003
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Immunization Effectively Reduces Amyloid Deposition in FcRγ-/-Knock-Out Mice

Abstract: Direct immunization with amyloid beta protein (Abeta) and passive transfer of anti-Abeta antibodies reduce Abeta accumulation and attenuate cognitive deficits in transgenic models of Alzheimer's disease (AD). The reduction in Abeta deposition has been proposed to involve microglial phagocytosis of Abeta immune complexes via Fc receptors (FcRs). We have examined the efficacy of Abeta immunization in amyloid precursor protein (APP) transgenic mice crossed into FcR-gamma chain knock-out mice (FcRgamma-/-). As mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
154
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(167 citation statements)
references
References 34 publications
9
154
1
3
Order By: Relevance
“…Several studies have proposed a microglial phagocytosis mechanism of amyloid clearance, in which antibodies bound to A␤ also interact with Fc receptors (FcR) on microglial cells to initiate microglial phagocytosis of antibody-bound A␤ and subsequently clear amyloid plaques (10,38,46,54). However, we and others have previously demonstrated a reduction of the parenchymal plaque burden by mechanisms that are independent of microglial function (55)(56)(57)(58). In the current study, microglia were activated with both systemic-and icv-delivered anti-A␤ IgG 1 , and may partially mediate the clearance of parenchymal plaques in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proposed a microglial phagocytosis mechanism of amyloid clearance, in which antibodies bound to A␤ also interact with Fc receptors (FcR) on microglial cells to initiate microglial phagocytosis of antibody-bound A␤ and subsequently clear amyloid plaques (10,38,46,54). However, we and others have previously demonstrated a reduction of the parenchymal plaque burden by mechanisms that are independent of microglial function (55)(56)(57)(58). In the current study, microglia were activated with both systemic-and icv-delivered anti-A␤ IgG 1 , and may partially mediate the clearance of parenchymal plaques in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…After centrifugation at 4 °C at 100,000 × g for 1 h, the supernatant was collected and stored at −80 °C until assayed. Brain samples were run in triplicate on ELISA plates coated with a monoclonal anti-Aβ1-16 antibody (kindly provided by Dr. William Van Nostrand, Stony Brook University, Stony Brook, NY) and detection was by monoclonal HRP conjugated anti-Aβ1-40 (MM32-13.1.1) and anti-Aβ1-42 (MM40-21.3.1) antibodies (kindly provided by Dr. Christopher Eckman, Mayo Clinic Jacksonville, Jacksonville, CA) [9,28,37]. For standards, Aβ1-40 and Aβ1-42 (Bachem California, Inc., Torrance, CA) were used after a pretreatment with HFIP to prevent fibril formation.…”
Section: Aβ Elisamentioning
confidence: 99%
“…15 However, a recent study indicated that FcR-mediated uptake of anti-Ab immune complexes is not required for the attenuation of Ab deposition after Ab1-42 immunization in Tg mice. 26 McLaurin et al 27 demonstrated antibody inhibition of Ab fibrillogenesis and cytotoxicity without eliciting an inflammatory response. We speculate that not only FcR-mediated phagocytosis through Ig G but also non-FcR-mediated clearance mechanism for amyloid deposition might as well effectively attenuate TTR deposition in V30M Tg mice.…”
Section: Immunization In Fap H Terazaki Et Almentioning
confidence: 99%